Adoptive cell therapy against tumor immune evasion: mechanisms, innovations, and future directions - Ruan, Liqin; Wang, Lu (Frontiers in Oncology, 2025)
Tumors employ a range of strategies to evade detection and eradication by the host’s immune system. These include downregulating antigen expression, altering antigen presentation processes, and inhibiting immune checkpoint pathways. etc. Adoptive Cell Therapy (ACT) represents a strategy that boosts anti-tumor immunity. This is achieved by amplifying or genetically engineering immune cells, which are either sourced from the patient or a donor, in a laboratory setting. Subsequently, these cells are reintroduced into the patient to bolster their immune response against cancer. ACT has successfully restored anti-tumor immune responses by amplifying the activity of T cells from patients or donors. This review focuses on the mechanisms underlying tumor escape, including alterations in tumor cell antigens, the immunosuppressive tumor microenvironment (TME), and modulation of immune checkpoint pathways. It further explores how ACT can avddress these factors to enhance therapeutic efficacy. Additionally, the review discusses the application of gene-editing technologies (such as CRISPR) in ACT, highlighting their potential to strengthen the anti-tumor capabilities of T cells. Looking forward, the personalized design of ACT, combined with immune checkpoint inhibitors and targeted therapies, is expected to significantly improve treatment outcomes, positioning this approach as a key strategy in the field of cancer immunotherapy.